THE ROLE AND IMPACT OF FAMILY VISITS ON PRISONERS - Bardhi, Krenar (E-Journal VFU, 2026)
This article analyzes the importance of family contacts in maintaining emotional stability of prisoners, their impact on reducing recidivism, and their role in the process of resocialization. Through an analysis of the international and national legal framework, as well as the jurisprudence of the European Court of Human Rights, it is argued that family contacts represent not only a fundamental right but also an effective instrument for rehabilitation. The article also addresses contemporary developments, such as the use of technology during the COVID-19 pandemic, highlighting their impact on the penitentiary system.